3D quasi-passive walking of bipedal robot with flat feet: quasi-passive walker driven by antagonistic pneumatic artificial muscle. (1st January 2013) - Fujimoto, Shinsaku; Kinugasa, Tetsuya; Yoshida, Koji; Watanabe, Hiroyuki
In this paper, we develop the three-dimensional quasi-passive walker with flat feet which is driven by antagonistic pneumatic artificial muscle. An antagonistic pneumatic system is used as joint actuators of linkage mechanisms which control the torque, joint stiffness and position simultaneously. We examine the structure of an ankle, the control method of an antagonistic pneumatic system and gait analysis using centre of pressure (COP) and rollover shape (ROS). As a result, a three-dimensional quasi-passive walking is realisable by means of adjusting the stiffness of an ankle joint. The average gaits were obtained with the travel distance 1, 350 mm, the stride of a step: 210 mm, and the number of steps: six steps. It was demonstrated that the quasi-passive walking is stabilised when both the robotic motions in a lateral plane and in a sagittal plane are synchronised. The COP behaviour of robot gait was almost the same trend of human COP. It was demonstrated that rollover shapes of the sagittal and lateral plane could be adjusted by the internal pressure of the antagonistic pneumatic mechanism.